Injuries to the Immature Optic Radiation Show Correlated Thinning of the Macular Ganglion Cell Layer - Lennartsson, Finn; Nilsson, Maria; Flodmark, Olof; Jacobson, Lena; Larsson, Jonas (Frontiers in Neurology, 2018)
Injuries to the immature optic radiation are associated with thinning of the retinal nerve fibre layer and corresponding visual field defects. The aim of the current study was to seek evidence for causal retrograde trans-synaptic degeneration by exploring the correspondence between the localization and extension of the injury to the optic radiation and the structure of the macular ganglion cell complex, and the relation to visual field function. Seven adults (age range 18-35) with visual dysfunction secondary to white-matter damage of immaturity and six healthy adults (age range 22-33) underwent MRI. Fibre tractography was used to generate the geniculate projections to the dorsal and ventral striate cortex, delineated by retinotopic functional MRI mapping. The structure of the macular ganglion cell complex was measured with ocular coherence tomography. The tractography showed overlaps between the dorsal and ventral geniculo-striate projections. However, in four patients with inferior visual field defects, the dorsal projections were to a large extent traversing the space normally solely occupied by ventral projections. This is consistent with structural changes to the optic radiation, and suggests of re-organisation upon injury. Diffusion parameters were significantly different between patients and controls, and most pronounced in the dorsal geniculo-striate projections, with a pattern indicating primary injury. The macular ganglion cell complex was significantly thinner in the patients and most pronounced in the superior sectors; a pattern particularly evident in the four patients with inferior visual field defects. The ratio of the mean thickness of the macular ganglion cell complex in the superior and inferior sectors significantly correlated with the axial and mean diffusivities in the contra- and ipsilateral dorsal striate projections. The results suggest a causal link between injuries to the superior portion of the immature optic radiation and secondary thinning in the macular ganglion cell complex, resulting in inferior visual field defects.